Modelling and optimization of rebound resilience and hardness of defatted rice bran/calcium carbonate-filled NR vulcanisates - Moonchai S. (2014)
Hardness and rebound resilience of natural rubber (NR) vulcanisates filled with defatted rice bran (DRB)/calcium carbonate (CaCO3) were modelled and optimized. Second-order polynomial functions were generated to model the properties and to generate contour plots. Predicted properties of NR vulcanisates showed good agreement with experimental results. Hardness of filled-NR vulcanisates increased with filler loading, whereas rebound resilience decreased. At a fixed hardness level, lower CaCO3 loading can be used with partial DRB replacement. DRB incorporation into rubber compounds can improve their stiffness. Contour plots were used to identify DRB and CaCO 3 level ranges for achieving optimum hardness and rebound resilience. © 2013 Elsevier Ltd. All rights reserved.